2017
DOI: 10.1016/j.soilbio.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Interactive plant functional group and water table effects on decomposition and extracellular enzyme activity in Sphagnum peatlands

Abstract: Peatland decomposition may be altered by hydrology and plant functional groups (PFGs), but exactly how the latter influences decomposition is unclear, as are potential interactions of these factors. We used a factorial mesocosm experiment with intact 1 m 3 peat monoliths to explore how PFGs (sedges vs Ericaceae) and water table level individually and synergistically affect decomposition processes. Decomposition was measured using litter bags at three depths filled with cellulose strips to mimic decomposition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 66 publications
(51 reference statements)
1
25
0
1
Order By: Relevance
“…This is supported by the significant but weak regression between GEP and DOC concentration, E2/E3 and SUVA, particularly across sites experiencing drainage (Figure 4). The results of the RDA analysis suggest that the changing DOC dynamics were specifically linked to the shift from a largely Sphagnum- (Wiedermann, Kane, Potvin, & Lilleskov, 2017). Although this was not specifically investigated in the present study, suppression of decomposition could also result in the observed shift in the DOC pool towards smaller, less aromatic molecules generally associated with fresh plant inputs.…”
Section: Links Between Vegetation Productivity and Doc Concentratiomentioning
confidence: 66%
See 1 more Smart Citation
“…This is supported by the significant but weak regression between GEP and DOC concentration, E2/E3 and SUVA, particularly across sites experiencing drainage (Figure 4). The results of the RDA analysis suggest that the changing DOC dynamics were specifically linked to the shift from a largely Sphagnum- (Wiedermann, Kane, Potvin, & Lilleskov, 2017). Although this was not specifically investigated in the present study, suppression of decomposition could also result in the observed shift in the DOC pool towards smaller, less aromatic molecules generally associated with fresh plant inputs.…”
Section: Links Between Vegetation Productivity and Doc Concentratiomentioning
confidence: 66%
“…These shifts appear to be linked not only to higher deposition of DOC into the rhizosphere, but also changes in belowground carbon and nitrogen cycling related to higher polyphenol concentration and fungal abundance at sites with greater shrub cover. The decomposition of complex organic molecules may also be slowed in the presence of Ericaceous shrubs, likely linked to the abundance of ectomycorrhizal fungus (Wiedermann, Kane, Potvin, & Lilleskov, ). Although this was not specifically investigated in the present study, suppression of decomposition could also result in the observed shift in the DOC pool towards smaller, less aromatic molecules generally associated with fresh plant inputs.…”
Section: Discussionmentioning
confidence: 99%
“…In bog ecosystems, decomposition of recalcitrant compounds associated with the breakdown of Sphagnum could be analogous to prior models of aromatic lignin decomposition (Straková et al, ; cf. Wiedermann, Kane, Potvin, et al, ; Worrall et al, ). The strong negative relationships between SUVA254 (an indicator of aromatic C) and Eh7, as well as between SUVA254 and E4:E6 presented herein (Figure ) are consistent with increased breakdown of aromatic biomolecules co‐occurring with the synthesis of larger macromolecules at higher Eh.…”
Section: Discussionmentioning
confidence: 99%
“…The Ericaceae produce recalcitrant litter (Cornelissen, 1996) and have mycorrhizal fungi, which possess some oxidative extracellular enzymes but lack peroxidase enzyme activity (Cairney & Burke, 1998;Cairney & Meharg, 2003); these factors have an inhibitory effect on peat decomposition (Read et al, 2004) thus promoting hummock formation and creation of microsites that are more likely to be above the WT (Belyea & Malmer, 2004;Ohlson & Dahlberg, 1991). As such, there are interactive effects between altered hydrology and plant functional groups, which have been shown to influence decomposition dynamics in peat (Wiedermann, Kane, Potvin, et al, 2017). However, the interactive effects of changes in peat saturation or vegetation community on oxygen supply and redox environment remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Moisture also has the potential to affect litter decomposition and nutrient cycling rates. Decomposition is usually slow under very wet (Wiedermann, Kane, Potvin, & Lilleskov, ) or dry conditions (Vogel, Eisenhauer, Weigelt, & Scherer‐Lorenzen, ), which could result in lower soil nutrient availability to plants and hence the production of lower‐quality root and shoot litter at the extreme ends of the moisture gradient (Reich, ). This could result in more negative plant–litter feedbacks for fast‐growing plants that are more dependent on high nutrient inputs and less able to tolerate harsh conditions (Figure b).…”
Section: Abiotic Driversmentioning
confidence: 99%